Phospho-Form Specific Substrates of Protein Kinase B (AKT1) - McKenna, McShane; Balasuriya, Nileeka; Zhong, Shanshan; Li, Shawn Shun-Cheng; O'Donoghue, Patrick (Frontiers in Bioengineering and Biotechnology, 2021)
Protein kinase B (AKT1) is hyper-activated in diverse human tumors. AKT1 is activated by phosphorylation at two key regulatory sites, Thr308 and Ser473. Active AKT1 phosphorylates many, perhaps hundreds, of downstream cellular targets in the cytosol and nucleus. AKT1 is well known for phosphorylating proteins that regulate cell survival and apoptosis, however, the full catalog of AKT1 substrates remains unknown. Using peptide arrays, we recently discovered that each phosphorylated form of AKT1 (pAKT1S473, pAKT1T308, and ppAKT1S473,T308) has a distinct substrate specificity, and these data were used to predict potential new AKT1 substrates. To test the high-confidence predictions, we synthesized target peptides representing putative AKT1 substrates. Peptides substrates were synthesized by solid phase synthesis and their purity was confirmed by mass spectrometry. Most of the predicted peptides showed phosphate accepting activity similar to or greater than that observed with a peptide derived from a well-established AKT1 substrate, glycogen synthase kinase 3 β (GSK-3β). Among the novel substrates, AKT1 was most active with peptides representing PIP3-binding protein Rab11 family-interacting protein 2 and cysteinyl leukotriene receptor 1, indicating their potential role in AKT1-dependent cellular signaling. The ppAKT1S473,T308 enzyme was highly selective for peptides containing a patch of basic resides at -5, -4, -3 and aromatic residues (Phe/Tyr) at +1 positions from the phosphorylation site. The pAKT1S473 variant preferred more acidic peptides, Ser or Pro at +4, and was agnostic to the residue at -5. The data further support our hypothesis that Ser473 phosphorylation plays a key role in modulating AKT1 substrate selectivity.